2000
DOI: 10.1073/pnas.090101397
|View full text |Cite
|
Sign up to set email alerts
|

Computation, prediction, and experimental tests of fitness for bacteriophage T7 mutants with permuted genomes

Abstract: We created a simulation based on experimental data from bacteriophage T7 that computes the developmental cycle of the wildtype phage and also of mutants that have an altered genome order. We used the simulation to compute the fitness of more than 10 5 mutants. We tested these computations by constructing and experimentally characterizing T7 mutants in which we repositioned gene 1, coding for T7 RNA polymerase. Computed protein synthesis rates for ectopic gene 1 strains were in moderate agreement with observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 40 publications
7
106
0
Order By: Relevance
“…As a test of the T7 virtual model, several constructs were made in which the RNAP gene was moved further from the left end of the genome. The most extreme shift was to 66-72% from the left end, and the predicted delays in life cycle were qualitatively, albeit not quantitatively, matched by the observed delays (Endy et al, 2000).…”
Section: Experiments In Regulatory Evolutionmentioning
confidence: 78%
See 3 more Smart Citations
“…As a test of the T7 virtual model, several constructs were made in which the RNAP gene was moved further from the left end of the genome. The most extreme shift was to 66-72% from the left end, and the predicted delays in life cycle were qualitatively, albeit not quantitatively, matched by the observed delays (Endy et al, 2000).…”
Section: Experiments In Regulatory Evolutionmentioning
confidence: 78%
“…In addition, two compensatory mutations evolved before, and 15 (affecting 10 genes) and 1 promoter change evolved subsequent to the recombination, but there is no basis for understanding the relevance of any of these mutations to the reordered genome. Reflecting our lack of complete understanding of T7, the virtual model v2.5 (Endy et al, 2000) predicted fitness loss due to the observed final gene order to be much smaller than actually observed.…”
Section: Expected Evolutionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the 3Ј end of the mouse hepatitis virus genome, gene order rearrangements reduce the number of recombinant viruses recovered (24). New regulatory circuits have been designed to control the lysogenic and lytic phases of infection in phage (25,26), and genome order has been remodeled in some phage and mammalian viruses (27,28). However, complete redesign of a virus transcription circuit has not been reported.…”
Section: Discussionmentioning
confidence: 99%